Impact of COVID-19 on Preventable Blindness Detection in Bali, Indonesia - Lestari, Ni Putu Dharmi; Gede Benny Setia Wirawan; I Putu Rustama Putra; Ni Wayan Sedani; Cynthia Dewi M (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2024)
Introduction: WHO, and the Indonesian government, have agreed to a plan to eradicate preventable blindness by 2020 in VISION 2020. However, the COVID-19 pandemic has caused a strain on the healthcare system. It is difficult to assess the impact of the pandemic on preventable blindness. Here we approach the issue by evaluating hospital visits for visual impairments in one regency in Bali, Indonesia. Methods: We collected outpatient visit records from three hospitals providing ophthalmologic clinics in Tabanan, Bali, Indonesia, a regency of 445 thousand people. We then conducted a descriptive analysis of the general changes in outpatient visits to these clinics and changes observed in different diagnoses identified as causes for preventable blindness. Results: The result showed a 35% downtrend in outpatient visits to the ophthalmologic clinic throughout the provinces. A more pronounced downtrend (45.22%) was observed for one public hospital that also serves as a COVID-19 referral hospital compared to private hospitals (around 30% each). By diagnoses, visits for cataracts were shown with a less severe downtrend compared to glaucoma, pterygium, and refractive disorders. Conclusion: Our study found a downtrend in outpatient visits for visual impairment in ophthalmologic clinics, which may be attributed to COVID-19 preventive measures by the hospital as well as patient reluctance due to fear of COVID-19 transmission. Public health communication needs to address this fear to recover patient confidence while maintaining vigilance in practicing COVID-19 preventive behavior.